Time-resolved molecular measurements reveal changes in astronauts during spaceflight - Zheng, Minzhang; Charvat, Jacqueline; Zwart, Sara R.; Mehta, Satish K.; Crucian, Brian E.; Smith, Scott M.; He, Jin; Piermarocchi, Carlo; Mias, George I. (Frontiers in Physiology, 2023)
From the early days of spaceflight to current missions, astronauts continue to be exposed to multiple hazards that affect human health, including low gravity, high radiation, isolation during long-duration missions, a closed environment and distance from Earth. Their effects can lead to adverse physiological changes and necessitate countermeasure development and/or longitudinal monitoring. A time-resolved analysis of biological signals can detect and better characterize potential adverse events during spaceflight, ideally preventing them and maintaining astronauts' wellness. Here we provide a time-resolved assessment of the impact of spaceflight on multiple astronauts (n=27) by studying multiple biochemical and immune measurements before, during, and after long-duration orbital spaceflight. We reveal spaceassociated changes of astronauts' physiology on both the individual level and across astronauts, including associations with bone resorption and kidney function, as well as immune-system dysregulation.